2006
DOI: 10.1007/bf02607055
|View full text |Cite
|
Sign up to set email alerts
|

Regularization in statistics

Abstract: This paper is a selective review of the regularization methods scattered in statistics literature. We introduce a general conceptual approach to regularization and fit most existing methods into it. We have tried to focus on the importance of regularization when dealing with today's high-dimensional objects: data and models. A wide range of examples are discussed, including nonparametric regression, boosting, covariance matrix estimation, principal component estimation, subsampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
131
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(133 citation statements)
references
References 106 publications
0
131
0
2
Order By: Relevance
“…There exists a vast literature for statistics that describes the importance of regularization, particularly when analyzing high-dimensional data with small sam-ples (see Bickel & Li, 2006, for a detailed overview). Regularization is a useful technique for producing more accurate estimates by the use of prior knowledge.…”
mentioning
confidence: 99%
“…There exists a vast literature for statistics that describes the importance of regularization, particularly when analyzing high-dimensional data with small sam-ples (see Bickel & Li, 2006, for a detailed overview). Regularization is a useful technique for producing more accurate estimates by the use of prior knowledge.…”
mentioning
confidence: 99%
“…Golan thanks the Edwin T. Jaynes International Center for Bayesian Methods and Maximum Entropy for partially supporting this project. We also want to thank the referees for their comments, for their careful reading of the manuscript and for pointing out reference [26] to us. Their comments improved the presentation considerably.…”
Section: Acknowledgmentsmentioning
confidence: 98%
“…If, in addition, the data are ill-conditioned, one often has to resort to the class of regularization methods (e.g., Hoerl and Kennard [19] O'Sullivan [20], Breiman [21], Tibshirani [22], Titterington [23], Donoho et al [24]; Besnerais et al [25]. A reference for regularization in statistics is Bickel and Li [26]. If some prior information on the data generation process or on the model is available, Bayesian methods are often used.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is particularly appealing for dealing with large-dimensional problems. A review article on regularization in statistics can be found in Bickel and Li (2006). This section overviews some regularized estimation methods.…”
Section: Regularized Estimation With Independent Datamentioning
confidence: 99%